Expert Assessment of Healthcare Organizations' Sources of Supply Chain Management - E.V. Kostyrin (International Journal of Supply Chain Management, 2019)
This research article analyzes the main sources of financing activities of healthcare organizations, and, using the analytic hierarchy process, conducts a comparative analysis of compulsory health insurance (CHI), voluntary health insurance (VHI), and medical savings accounts (MSAs) as sources of financing for medical care. The necessity of implementing MSA in domestic healthcare financing is substantiated. To make an expert assessment, the article develops a criteria tree consisting of the following: novelty, supply chain strategy, practical feasibility, the consideration of interests of different social groups, social fairness, the freedom to choose a healthcare organization, competitiveness, and economic efficiency. The article describes in detail the mechanism of constructing the pairwise comparison matrix according to the author's criteria in compliance with their influence on the overall goal of the expert assessment. It also, shows an example of calculating the maximum eigenvalue of the pairwise comparison matrix, the matrix conformity index and the conformity ratio. Issues of forming a quality expert group are considered. The questionnaire survey resulted in the following distribution of expert opinions (in percent, characterizing the degree of preference of the corresponding source of financing for healthcare organizations) - CHI 24.90%; VHI 28.62%; MSA 46.48% - which shows the perspective and public support for the transition of financing for domestic healthcare organizations to MSA.